Antioxidant and Probiotic Properties of Lactobacilli and Bifidobacteria of Human Origins - Kim, Hyemin; Kim, Jin-Seong; Kim, YongGyeong; Jeong, Yulah; Kim, Ji-Eun; Paek, Nam-Soo; Kang, Chang-Ho (Biotechnology and bioprocess engineering, 2020)
Oxidative stress can cause various diseases including inflammation, neurological disorders, cancer, diabetes, and cardiovascular diseases. Due to the current search for natural antioxidants, probiotics have received increasing scientific interest and are facing a growing industrial demand. Although various strains of lactobacilli and bifidobacteria are currently used in numerous health food supplements, their antioxidative activities have been relatively poorly identified. Therefore, in this work, we evaluated the in vitro effect of antioxidative activities (through assays of 2,2-diphenyl-l-picrylhydrazyl (DPPH) and 2,2′-azinobis-(3-ethylbenzothiazorine-6-sulfonate) (ABTS) radical scavenging) and probiotic functional properties (cell viability in a simulated gastrointestinal tract, enzyme production, carbohydrate availability, and safely assessments) of Lactobacillus spp. and Bifidobacterium spp. isolated from human origins. From the nitric oxide (NO) assay screening, four strains (Bifidobacterium animalis subsp. lactis MG741, B. breve MG729, L. reuteri MG505, and L. rhamnosus MG316) were selected based on the yield amount of ferment productivity (> × 10 10 CFU/g) and showed high antioxidant activities ranging from 22.2% to 38.2% in DPPH free radical scavenging, and 50.0% to 93.6% in ABTS radical scavenging. Regarding their functional properties as probiotics, these four strains were resistant to simulated gastric (pH 3 and 4) and intestinal fluids (pH 7 and 8), and showed potential for the promotion of health based on hemolysis, auto-aggregation, antibiotic susceptibility, enzyme production, and biochemical profiles. Altogether, our results showed that the selected probiotic strains may be good candidates as food ingredients to mitigate oxidative stress-related symptoms.